Antimicrobial effects of new tetrahydrofurans - Shanmugha Samy; Manikandan Alagumuthu; Milind Shrinivas Dangate (Elsevier, 2024)
The increasing challenge of antimicrobial resistance (AMR) necessitates abrupt attention to discovering a new class of antimicrobials. In this study, we made efforts to prepare some fluoro-phenyl tetrahydrofurans-based DNA gyrase inhibitors as anti-microbial agents. To obtain the title compounds difluoro phenyl tetrahydrofurans (1-12), we used fluorophenyl-tetrahydrofuran and methyl benzenesulfonate to react with isoxazole derivatives and heterocyclic compounds bearing secondary amines in the presence of dimethylformamide (DMF) and sodium hydride (NaH) or potassium carbonate (K2CO3). The compounds were obtained in moderate to excellent yields and were characterized with FTIR, HRMS, NMR, etc. Among all compounds (1-12), compounds 1, 2, 11, and 12 were active against various Gram-positive and Gram-negative bacteria at a low concentration (MIC ranged between 1.25 and 9.75 μg/mL) and displayed low toxicity towards mammalian cells. We testified the in vitro DNA gyrase inhibitory potential for these compounds. A molecular docking study and an ADMET assessment study were carried out to understand the mode of interaction of ligand-DNA gyrase. In conclusion, we screened the compounds 1, 2, 11, and 12 for further clinical and pre-clinical studies.